New Two-Dimensional Materials Obtained by Functionalization of Boron Graphdiyne Layers with Nickel - Estefanía Germán; María J. López; Julio A. Alonso (Nanomaterials)
The decoration of hexagonal boron graphdiyne (BGDY) layers with Ni atoms has been investigated by density functional calculations. For one, two, and three Ni atoms per hexagon, the BGDY structure is approximately maintained. Decoration with six Ni atoms per hexagon leads to the formation of a novel, very stable two-dimensional material in which the hexagonal structure of BGDY is substantially distorted. The Ni-doped materials have a semiconductor character, and the electronic band gap width can be tailored by varying the amount of adsorbed Ni. BGDY-2Ni, BGDY-3Ni, and BGDY-6Ni have electronic band gaps promising for infrared detectors. This work shows that computer simulation helps to discover new materials by the functionalization of layered carbon materials with metal atoms.